Susceptibility to cytomegalovirus, parvovirus B19 and age‐dependent differences in levels of rubella antibodies among pregnant women. Issue 5 (30th September 2013) - Barlinn, Regine; Vainio, Kirsti; Samdal, Helvi Holm; Nordbø, Svein Arne; Nøkleby, Hanne; Dudman, Susanne G.
Abstract Infections caused by cytomegalovirus (CMV), parvovirus B19 (B19), and rubella can lead to serious complications in pregnant women. The aim of this study was to determine the susceptibility to CMV, B19, and rubella antibodies in pregnant women in Norway. Consecutive sera samples were collected from pregnant women in two different regions in Norway. Sera were collected from age groups; ≤19, 20–24, 25–29, 30–34, 35–39, and ≥40 years old. Of the 2, 000 pregnant women tested, anti‐CMV IgG was positive in 62.8% anti‐parvovirus B19 IgG in 59.7% and anti‐rubella IgG in 94.4%. CMV IgG susceptibility has decreased in pregnant women less than 30 years of age, from 60% in a study conducted in 1973–1974 to 37.2% in present study. There was a significant difference in CMV IgG seropositivity rate between the two regions (58.6% and 67.1%). Serum levels of rubella IgG was lowest in age group 25–29 years with a positivity rate of 91.0%. Women born before vaccination with two doses of MMR started, had both a higher positivity rate and significantly higher levels of rubella antibody titre, 96.1% and 82.2 IU/ml compared to those born after 92.9% and 41.7 IU/ml. Significantly lower anti‐rubella IgG titre found in the youngest age groups highlights the need for continued antenatal screening. A considerable increase in anti‐CMV‐IgG seropositivity rate was observed and might be associated with higher rate of breastfeeding and a higher percentage attending day‐care centres. J. Med. Virol. 86:820–826, 2014. © 2013 Wiley Periodicals, Inc.